Effect of dietary vanadium supplementation on growth performance, mineral balance and antioxidant activity in male Sahiwal calves - SINGH, DIGVIJAY; DATT, CHANDER; MISHRA, AKASH; SHIVANI, SWATI; GUPTA, RITIKA; MANI, VEENA (The Indian Journal of Animal Sciences, 2019)
The study was aimed to examine the effect of supplementation of sodium metavandate (NaVO3) as source of vanadium on DMI intake, growth performance, antioxidant activity, level of mineral in plasma and their balance in male Sahiwal calves. The vanadium content in maize (Zea mays) and bajra (Pennisetum glaucum) grains was 58 ppb and 55 ppb while in berseem (Trifolium alexandrinum) and mustard (Brassica campestris) fodder it was 8.37 and 7.24 ppm, respectively. Male Sahiwal calves (20) of comparable age (6Â±0.82 months) and body weight (71Â±8.06 kg) were randomly allotted to 4 different treatments with replication of 5 animals in each. Supplementation was done with 0, 2, 4 and 8 ppm of vanadium in groups T1, T2, T3 and T4, respectively, for 120 days. Blood samples were collected at monthly intervals to examine antioxidant activity in blood, plasma and mineral levels. Feed consumption (DM intake, DM intake% BW) and growth rate did not show any significant effect of vanadium supplementation. Glutathione peroxidase activity was higher in groups T3 and T4 as compared to T1 and T2 whereas, SOD and catalase activity was similar in all the groups. Excretion and absorption patterns of Ca, P, Cu and Fe and their plasma levels were similar in different groups. However, vanadium and Zn balance and their plasma levels increased due to vanadium supplementation. The present study revealed that in growing calves, vanadium supplementation showed enhanced glutathione peroxidise activity, plasma Zn and vanadium levels.